OPTIMIZATION OF THE EDUCATIONAL PROCESS USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES (Uzbekistan Open Conference, 2026)
The article explores theoretical and practical aspects of optimizing the educational process using artificial intelligence technologies. It examines personalized learning, automated assessment, learning analytics, and intelligent learning environments. The findings demonstrate that artificial intelligence significantly improves the quality and efficiency of education.